2014
DOI: 10.1016/j.maturitas.2014.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Sex and gender differences in the causes of dementia: A narrative review

Abstract: This is a narrative review of new ideas and concepts related to differences between men and women in their risk of developing dementia or Alzheimer's disease (AD). We introduce the concept of dimorphic neurology and the distinction between sex and gender. We then provide three examples of risk factors related to sex and gender from the literature. Apolipoprotein E genotype is equally common in men and women but has a stronger effect in women. Apolipoprotein E genotype is a biological factor that cannot be modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
118
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(124 citation statements)
references
References 59 publications
5
118
0
1
Order By: Relevance
“…In addition, they may result from gender related differences in personality or behavior (subjective component of gender) or from differences due to social, cultural, and legal factors (societal component of gender). 24,25 The effects of sex and gender on multimorbidity are an important area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they may result from gender related differences in personality or behavior (subjective component of gender) or from differences due to social, cultural, and legal factors (societal component of gender). 24,25 The effects of sex and gender on multimorbidity are an important area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…However, other authors have reported different findings; for example, one study estimated that almost two-thirds of individuals diagnosed with Alzheimer disease are women 14. These conflicting findings may result from the inclusion of small samples at the upper range of the age distribution, the use of different diagnostic criteria, and differences due to specific social, culture, and historical factors 1516…”
Section: Discussionmentioning
confidence: 99%
“…Significant differences were evident between OA, depression, GID, and hematologic diseases, which were more prevalent among women, and genitourinary diseases and excessive use of alcohol, which were more prevalent among men. Women, due to menopause and the consequent decline in estrogen levels, have an increased risk of cognitive impairment and the prevalence of other diseases [31]. Of note, a highly significant correlation (25%) was evident between CDR ≄1 and GID+.…”
Section: Discussionmentioning
confidence: 99%